Chemical tuning reveals a cation–π gating bridge between the voltage-sensor and pore domains in the K v 7.1 potassium channel - Miranda E. Schene; Christopher A. Ahern (Proceedings of the National Academy of Sciences, 2026)
K v 7.1 is a cardiac voltage-gated potassium channel that underlies the delayed rectifier current (I KS ) in the heart. The slow response to membrane depolarization is a hallmark feature of this channel’s physiology, yet the mechanistic basis of how voltage promotes the open potassium conducting state is unknown. We focused on previously identified aromatic residues which might couple the pore and voltage-sensing domains (VSDs) by using a chemical tuning approach whereby aromatic residues are modified by serial fluorination. The data show that serial fluorination at one site (F232 on the S4 helix, within the VSD) resulted in a stepwise voltage-gating shift, where each added fluorine atom further biased channel opening to more negative voltages. Mutant-cycle analysis of proximal positively charged amino acids indicates that F232 likely forms a cation–π interaction with K285, a residue at the tip of the S5 segment in the pore domain. Using cryoelectron microscopy, a partial structure of the F232 penta-F-Phe K v 7.1 (KCNQ1) open channel was resolved to 6 Å. The data support a gating mechanism whereby the F232–K285 cation–π interaction represents an intermediate activated state that is broken prior to channel opening.